Behaviour of the buccal crestal bone levels after immediate placement of implants subjected to immediate loading. Issue 3 (March 2015) - Lemes, H. deP.; Sartori, I.A. deM.; Cardoso, L.C.; Ponzoni, D.
Abstract The aim of this study was to measure changes in buccal alveolar crestal bone levels after immediate placement and loading of dental implants with Morse taper prosthetic abutments after tooth extraction. This study followed the STROBE guidelines regarding prospective cohort studies. The sample comprised 12 patients with a mean age of 45 years, in whom a central or upper lateral incisor was indicated for extraction. Prior to extraction, computed tomography (CT) analysis was carried out to assess the presence of the buccal bone crest. CT scans were performed at 24 h and at 6 months after immediate implant placement and immediate loading. The distance from the most apical point of the implant platform to the buccal bone crest was assessed at the two time points. The buccal bone crest height was evaluated at three points in the mesio-distal direction: (1) the centre point of the alveolus, (2) 1 mm mesial to the centre point, and (3) 1 mm distal to the centre point. The values obtained were subjected to statistical analysis, comparing the distances from the bone crest to the implant platform for the two time points. After 6 months there was a statistically significant, non-uniform reduction in height at the level of the crest of the buccal bone in the cervical direction. It is concluded that the buccal bone crest of the immediate implants that replaced the maxillary incisors underwent apical resorption when subjected to immediate loading.